Brown algae (Lessonia nigrescens, species complex) fisheries of northern Chile evaluated through the DPSIR approach: Social and economic impact of management strategies. (1st June 2022) - Berrios, Fernando; González, Jorge E.; Campos, Leonardo; Campbell, Daniel E.; Bonnail, Estefanía
Abstract: The kelp ( Lessonia nigrescens, species complex) resource is, in economic and social terms, one of the main benthic fisheries in northern Chile. The fishery for this resource is artisanal in character and operates under a free access regime. However, in response to increasing market demand extractive activity has expanded from the collection of dead plants to direct extraction. This resource has biologically-based management plans that include effort regulations and annual extraction quotas. However, the algal population has suffered strong fishing pressure, complicating the governance of this activity. This study assessed the fishery dynamics of the algal resource L. nigrescens complex in northern Chile over the last decade by means of the Driver-Pressure-State-Impact-Response (DPSIR) conceptual framework. The results showed that the fishery dynamics were affected by high international demand, which has promoted the fishing effort (pressure) in response to economic and social factors (driving forces). This scenario presents problems for the fishery due to a tendency towards resource overexploitation, negative effects on the state of benthic ecosystems, and negative economic "impacts" that occur as a result of reduced fishers' revenues, social conflict and ineffective fishery governance. The assessment of the fishery management of the algae L. nigrescens through the DPSIR framework in the coastal area of the Atacama Region allowed us to identify the main components that explain the trend towards the deterioration of this fishery over the last decade. Highlights: The Driver-Pressure-State-Impact-Response model was used to assess Lessonia nigrescens management plans in northern Chile. The current state of the fishery generates productive inefficiencies, high control costs and conflicts among fishers. Management measures were reviewed and summarized within the DPSIR framework.